Elder orphans on Facebook: Implications for mattering and social isolation. (February 2022) - Francis, Jess
Abstract: The number of older adults at risk for social disconnectedness, loneliness, and the negative mental and physical health outcomes associated with each will reach unprecedented size in the next decade. Elder orphans, or adults aged 65+ who live alone and are unmarried and childless, are particularly at risk for social isolation. Prior research has shown that social media use, specifically Facebook use, can provide individuals with access to social resources that promote well-being. To date, the research regarding Facebook use and its impact on loneliness is somewhat inconclusive. There have been studies with young adults, however, that suggest that Facebook use might promote the perception of mattering - a protective resource against loneliness. It is the aim of this study to assess how the modalities of Facebook can be harnessed in order to address the threat of loneliness among elder orphans through the promotion of mattering. This study employed online survey methodology among a sample of elder orphan Facebook users (n = 517). Results of this study show that Facebook activities were significantly and positively related to mattering and significantly and negatively related to loneliness among elder orphans. Highlights: Elder orphans are older adults (aged 65+) who are unmarried, living alone, and do not have children. Elder orphans are at greater risk for social isolation than other older adults. Social network sites such as Facebook can facilitate connection with social network ties and promote feelings of mattering. Through the mechanism of mattering, Facebook use is associated with reduced feelings of loneliness among elder orphans.